Intraoperative Angiography for Cranial Dural Arteriovenous Fistula - Pandey, P. (AJNR Am J Neuroradiol, 2011)
BACKGROUND AND PURPOSE: IA is a valuable adjunct during surgery for a variety of neurovascular diseases; however, there are no reported series describing IA for DAVFs. This study was undertaken to evaluate the safety and efficacy of IA for DAVFs. MATERIALS AND METHODS: A retrospective review of DAVF surgical cases during a 20-year period was conducted, and cases with IA were evaluated. Clinical details, surgical and angiographic findings, and postoperative outcomes were reviewed. The incidence of residual fistula on IAs, the utility of the surgical procedure, and the incidence of false-negative findings on IA were also determined. RESULTS: IA was performed in 29 patients (31 DAVFs) for DAVFs. The distribution of the fistulas was the following: transverse-sigmoid (n = 9), tentorial (n = 6), torcular (n = 3), cavernous sinus (n = 4), SSS (n = 4), foramen magnum (n = 3), and temporal-middle fossa (n = 2). Twelve patients had undergone prior embolization, while 6 patients had unsuccessful embolization procedures. Thirty-eight surgeries were performed for DAVF in 29 patients, and IA was performed in 34 surgeries. Forty-four angiographic procedures were performed in the 34 surgeries. Nine patients underwent multiple angiographies. In 11 patients (37.9%), IA revealed residual fistula after the surgeon determined that no lesion remained. This led to further exploration at the same sitting in 10 patients, while in 1 patient, further surgery was performed at a later date. False-negative findings on IA occurred in 3 patients (10.7%). CONCLUSIONS: IA is an important adjunct in surgery for DAVF. In this series, it resulted in further surgical treatment in 37.9% of patients. However, there was a 10% false-negative rate, which justified subsequent postoperative angiography.